Patient safety culture in neonatal intensive care units: A qualitative content analysis - Babaie, Mohadese; Nourian, Manijeh; Atashzadeh-Shoorideh, Foroozan; Manoochehri, Houman; Nasiri, Malihe (Frontiers in Public Health, 2023)
Background Safety culture, as an important and influential component of neonatal safety, can lay the ground for the provision of professional and quality care by creating a positive insight among workers. The present study aimed to explain the concept of safety culture and its dimensions from the perspective of the nurses and the physicians working in neonatal intensive care units (NICUs). Methods This qualitative directed content analysis study was carried out with 24 NICU physicians and nurses working in Tehran, Iran. These multicenter participants were selected through purposive sampling with maximum diversity in terms of demographic characteristics. The data was collected through in-depth semi-structured interviews and was analyzed using the deductive approach. The COREQ checklist was used for the comprehensive report of this study. Results The concept of patient safety culture in NICUs included achieving professional development, constructive interactions, organizational supportive climate, management's commitment to neonatal safety, planning and implementation of neonatal developmental care, which are extracted from 5 main categories, 10 generic categories and 21 sub-categories. Conclusion The dimensions of safety culture include procedures that, if promoted, could improve neonatal safety, reducing harm to neonates' health while expending less financial and human resources. Gaining knowledge of the status of these dimensions in wards and hospitals can give a purposeful direction to promote neonate health and policymaking.